Primary Alcohol‐Activated Human and Mouse Hepatic Stellate Cells Share Similarities in Gene‐Expression Profiles. Issue 4 (6th February 2020) - Liu, Xiao; Rosenthal, Sara Brin; Meshgin, Nairika; Baglieri, Jacopo; Musallam, Sami G.; Diggle, Karin; Lam, Kevin; Wu, Raymond; Pan, Stephanie Q.; Chen, Yibu; Dorko, Ken; Presnell, Sharon; et al.
Abstract : Alcoholic liver disease (ALD) is a leading cause of cirrhosis in the United States, which is characterized by extensive deposition of extracellular matrix proteins and formation of a fibrous scar. Hepatic stellate cells (HSCs) are the major source of collagen type 1 producing myofibroblasts in ALD fibrosis. However, the mechanism of alcohol‐induced activation of human and mouse HSCs is not fully understood. We compared the gene‐expression profiles of primary cultured human HSCs (hHSCs) isolated from patients with ALD (n = 3) or without underlying liver disease (n = 4) using RNA‐sequencing analysis. Furthermore, the gene‐expression profile of ALD hHSCs was compared with that of alcohol‐activated mHSCs (isolated from intragastric alcohol‐fed mice) or CCl4 ‐activated mouse HSCs (mHSCs). Comparative transcriptome analysis revealed that ALD hHSCs, in addition to alcohol‐activated and CCl4 ‐activated mHSCs, share the expression of common HSC activation ( Col1a1 [collagen type I alpha 1 chain], Acta1 [actin alpha 1, skeletal muscle], PAI1 [plasminogen activator inhibitor‐1], TIMP1 [tissue inhibitor of metalloproteinase 1], and LOXL2 [lysyl oxidase homolog 2]), indicating that a common mechanism underlies the activation of human and mouse HSCs. Furthermore, alcohol‐activated mHSCs most closely recapitulate the gene‐expression profile of ALD hHSCs. We identified the genes that are similarly and uniquely up‐regulated in primary cultured alcohol‐activated hHSCs and freshly isolated mHSCs, which include CSF1R (macrophage colony‐stimulating factor 1 receptor), PLEK (pleckstrin), LAPTM5 (lysosmal‐associated transmembrane protein 5), CD74 (class I transactivator, the invariant chain), CD53, MMP9 (matrix metallopeptidase 9), CD14, CTSS (cathepsin S), TYROBP (TYRO protein tyrosine kinase‐binding protein), and ITGB2 (integrin beta‐2), and other genes (compared with CCl4 ‐activated mHSCs). Conclusion: We identified genes in alcohol‐activated mHSCs from intragastric alcohol‐fed mice that are largely consistent with the gene‐expression profile of primary cultured hHSCs from patients with ALD. These genes are unique to alcohol‐induced HSC activation in two species, and therefore may become targets or readout for antifibrotic therapy in experimental models of ALD. Abstract : We identified genes in alcohol‐activated mHSCs from IG alcohol‐fed mice that are largely consistent with the gene‐expression profile of primary cultured hHSCs from patients with ALD. These genes are unique to alcohol‐induced HSC activation in two species, and therefore may become targets or readout for antifibrotic therapy in experimental models of ALD.